Dystocia In Iraqi Cross Breed cows: causes and Treatment - Sultan, Ali Shalash (The Iraqi Journal of Veterinary Medicine, 2010)
The study was conducted on 35 Cross breed cows. Three–Six years old suffering from dystocia in various regions of Baghdad province during 1996-2004. The incidence of dystocia was 29.16% (35 /120) from total calving cows. The result showed that the dystocia due to fetal and the dam were 85.71%(30/35) and 14.28%(5/35) respectively.The anterior presentation percentage from fetal dystocia cases was 93.3%(28/30) while the percentage of posterior presentation was 6.6% (2/30) from these cases. Cows delivered male and female calves were formed 77.14% (27/35) and 28.57% (10/35). The calves mortality percentage in both sex was 62.85% (22 / 35). The conclusion suggested that high incidence of dystocia due to fetus was in cows calving male calves .The manual repairing , correction and traction was the best methods when performed early, while Cesarean section was the pervecit especially in the cases accompanied with uterine involution and expulsion of uterine fluids that facilate parturition, as well as fetal over size or that can't be correct manually.